Transformation Model of Government Policy on Task Force Through Coronavirus Disease 2019 Pandemic Handling Strategy in the COVID Tourism Ambassador Program in South Sulawesi Province, Indonesia - Aslinda, Aslinda; Ibrahim, Muhammad Akmal; Palutturi, Sukri (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Various policies have been issued by the government regarding task force to accelerate coronavirus disease 2019 (COVID-19) handling, ranging from presidential decrees, ministerial decrees, governor decrees, followed by decisions from the implementing agencies regarding the policy outputs, and compliance of the target groups. AIM: This study aimed to identify and analyze changes in task force policies as well as strategies used in handling the COVID-19 pandemic through the Tourism Ambassador program in South Sulawesi which is considered as an effective model for handling COVID-19. METHODS: This research was conducted by applying qualitative method that emphasizes interpretation and phenomena holistically. The analysis used was the model of government policy transformation in the task force through the COVID-19 pandemic handling strategy in the COVID tourism ambassador program in South Sulawesi. This study was participated by informants (participants) who were involved in the COVID Ambassador Tourism Program in South Sulawesi. RESULTS: The Provincial Government of South Sulawesi has made policy changes, especially regarding the COVID-19 handling acceleration task force. There were various changes in the government regulatory policies related to the Regulation of the Minister of Health (Permenkes) of the Republic of Indonesia No. 09 of 2020 to Presidential Decree (Kepres) No. 11 of 2020 regarding regulations for Large-Scale Social Restrictions to accelerate the handling of COVID-19 in South Sulawesi. CONCLUSION: Changes in policy related to the acceleration of COVID-19 control and handling in South Sulawesi resulted in a policy output that showed a decrease in the number of COVID-19 positive cases. Implementing the strategy through the COVID-19 Tourism Ambassador program as a model for handling COVID-19 in South Sulawesi is the right strategy.